New High-Current Pulsed Ion Accelerator Facility INURA at Nazarbayev University: First Results and New Opportunities for Advanced Materials and Nanoscience; Surface Modification of Materials by Ion Beams (SMMIB-2019) - Tikhonov A. Alexander; Kaikanov M. Marat; Baigarin K. Kanat; Kozlovskiy (Kozlovsky) A. Artem; Akhtanova G. Gulnur; Waldron W. Will; Kwan J. Joe; Remnev (Remnyov) G. E. Gennady Efimovich; Zhuravlev M. V. Mikhail Valerievich (Biomedical and Industrial Applications. Invited Talks, 2019)
Заглавие с экрана